Marshall [videorecording (DVD)] - Boseman, Chadwick; Gad, Josh, 1981-; Hudson, Kate, 1979-; Brown, Sterling K.; Cromwell, James (Universal Pictures Home Entertainment, 2018)
About a young Thurgood Marshall, the first African-American Supreme Court Justice, as he battles through one of his career defining cases.